Position of the European Union in the Global Trade System - Jovićević Mladen; Janjetović Željko (ECONOMICS, 2017)
Only a few decades ago, the main drivers of globalization were the exchange of goods and capital flows, while the global trading system of today, fuelled by rapid technological changes increasingly bases itself on knowledge. The Key events - such as the use of the Internet and the increasingly important role of the rising countries economies - have contributed to a faster global exchange, but to a new nature as well. In order to illustrate the scope of the increase, perhaps it would be the best to mention the fact that in the 1970’s the share of trade in the world GDP amounted to 20%, whereas today it makes about one half. On the other hand, modern products represent compounds of raw materials, components, technologies and services originating from different areas and different continents, which has globalized the products themselves. In such conditions of the market competition, imposed by globalization and liberalization, for the European Union to remain as a leader, it had to prepare a sound and well-founded foreign policy strategy. The aim of this paper is to analyse the current position of the European Union in the global trading system, instruments of foreign trade policy, goals, foreign trade and the main challenges placed before the Union.